EFEKTIVITAS GROUP BEHAVIOR THERAPY TERHADAP CONVERSATIONAL SKILL PADA PASIEN SKIZOFRENIA TIPE RESIDUAL (STUDI KASUS PADA INSTANSI X) - Garvin Garvin (Universitas Bunda Mulia, 2016)
Schizophrenia residual type is one of schizophrenia types which is the symptoms of schizophrenia are no longer appears significantly. The schizophrenia patients are need to be prepared before they complete their treatment in a mental health institution and back into society. A skill that is needed by schizophrenia residual type is conversational skills. However, some of schizophrenia patients are encountering problems in learning the conversational skills. The aim of this research is to study the effectiveness of group behavior therapy into the conversational skills of schizophrenia residual type patients. The technique used in the therapy is modeling and shaping. Statistical test with significance p = 0,002 < 0,01 shows that group behavior therapy can improve conversational skills in schizophrenia residual type patients. However, there are some limitations in the study so further study is needed. Keywords: schizophrenia residual type; conversational skill; group behavior therapy